2011
DOI: 10.1080/17461391.2011.635704
|View full text |Cite
|
Sign up to set email alerts
|

Response timing in the lunge and target change in elite versus medium‐level fencers

Abstract: The aim of the present work is to examine the differences between two groups of fencers with different levéis of competition, élite and médium level. The timing parameters of the response reaction have been compared together with the kinetic variables which determine the sequence of segmented participation used during the lunge with a change in target during movement. A total of 30 male sword fencers participated, 13 élite and 17 médium level. Two forcé platforms recorded the horizontal component of the forcé … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 8 publications
9
53
1
4
Order By: Relevance
“…This conclusion is however in contradiction with the hypothesis that the additional stimulus will not have any significant influence on fencers RT increase. Similar findings supporting this theory were made by Gutierrez-Davila et al 26 . Their study shows that not even the difference in choice RT (CRT) among elite and sub-elite fencers was found out.…”
Section: Discussionsupporting
confidence: 80%
“…This conclusion is however in contradiction with the hypothesis that the additional stimulus will not have any significant influence on fencers RT increase. Similar findings supporting this theory were made by Gutierrez-Davila et al 26 . Their study shows that not even the difference in choice RT (CRT) among elite and sub-elite fencers was found out.…”
Section: Discussionsupporting
confidence: 80%
“…This was further than that noted by Gholipour et al, (2008), but similar to Gutierrez-Davila et al, (2011) (117 and 140 cm respectively). Compared to Guilhem et al, (2014), and acknowledging their lunge was preceded by a (small) step but our fencers were taller (~8 cm), distance travelled appears similar.…”
Section: A C C E P T E Dsupporting
confidence: 59%
“…The average lunge time (from initiation to sword contact with target) was 400 ± 8 ms. This was quicker than Gholipour et al, (2008), Gutierrez-Davila et al, (2011) and Guilhem et al, (2014) (1082, 601 and 1430 ms respectively). In the study of Gholipour et al, (2008), fencers were asked to lunge with no target to aim at, with time stopped at completion of the lunge, which can often follow the swords contact with the target as this may occur with the front foot still airborne.…”
Section: A C C E P T E Dcontrasting
confidence: 45%
See 1 more Smart Citation
“…reaction and movement times have been studied in fencing as specific kinetic task responses; however studies that focus on training protocols oriented to improve the process timing and subsequent kinetic response remain inconclusive (7). It has been reported that expert fencers are faster in discriminating the correct stimulus (4), whereas other studies have shown that elite fencers have a quicker response in choice reaction protocols in comparison to novice fencers (29,30).…”
Section: Discussionmentioning
confidence: 99%